Kinetic Study of Transesterification Reaction of Edible Oil Using Heterogenous Catalyst - Aljendeel, Haider; Borhan, Ehab; Al-Ani , Mohammed J. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
AlPO4 solid acid catalyst was prepared in order to use it in transesterification reaction of edible oil after supporting it with tungsten oxide. The maximum conversion of edible oil was obtained 78.78% at catalyst concentration (5gm.), temperature 70°Ϲ, 30/1 methanol/edible oil molar ratio, and time 5hr. The study of kinetics of the transesterification reaction of edible oil indicates that the reaction has an order of 3/2, while the value of activation energy for transesterification reaction is 51.367 kJ/mole and frequency factor equal 26219.13(L/ mol.minute).